IFPRI's Strategy for Latin America and the Caribbean - International Food Policy Research Institute (International Food Policy Research Institute, 2009)
The Latin America and Caribbean (LAC) region is host to some of the most difficult environments in the world, either because of altitude, climate, or topography, or because of huge inequalities in the distribution of land (the bottom 60 percent of landowners—those with the smallest landholdings—own only 4 percent of all land in the region), as well as striking income inequality in spite of economic growth as shown in Figure 1 (with an average Gini index score of 53.29 as compared to Asia and Eastern Europe, whose scores of 41.8 and 32.8, respectively, indicate far less income inequality). On the other hand, the LAC region provides researchers and policymakers with significant opportunities to learn from the successful structural reforms that most of the LAC countries have undertaken during the late 1980s and early 1990s. During these decades most Latin American countries went through significant reforms: they controlled inflation, sold off state enterprises, lowered tariffs, opened capital markets, reformed tax systems, deregulated financial markets, and lowered government deficits. Latin America’s increased economic openness has gone hand in hand with large financial inflows—particularly in the first half of the 1990s—and has brought new sources of economic growth. As a result, economies grew, inflation declined, and there was a big surge in foreign capital inflows. Although overall growth slowed after 1995, the region has experienced strong growth in the past five years, the best sustained performance since the 1970s. With the exception of a handful of countries, this growth has been accompanied by relatively modest inflation. Despite these positive results, virtually all Latin American countries share certain problems: uneven economic growth, unacceptably high poverty and malnutrition rates, and lagging agricultural growth. More than 60 percent of the region’s poor live in rural areas, where slow economic growth, unequal distribution of assets, inadequate public investment and public services, and vulnerability to natural and economic shocks are major policy issues resulting in severe poverty traps. The food price crisis of 2007–08 and the financial crises of 2009 exacerbated these problems. Although the region is fairly immune to external shocks—due to its higher foreign exchange liquidity; decreased public-sector and external borrowing needs; exchange rate flexibility; lower exposure to currency, interest rate, and rollover risks in public-sector debt portfolios; and more access to local currency loans—the food price and financial crises affected all the LAC countries in terms of inflation, especially food inflation, and in terms of credit constraints, specifically those related to trade costs. The impact was greatest on net importing countries (specifically, Central America and Mexico), and also on poor consumers in peri urban and rural areas. Before the crisis, most Latin American countries were on track to reach the Millennium Development Goal of halving the proportion of people who suffer from hunger by 2015; now, a significant number of countries will not be able to accomplish this goal. Furthermore, inflationary pressures will reappear and persist in coming years. After reviewing recent and current work in the region, this document will explain IFPRI’s research strategy for the LAC region, conceived with the intention to help policymakers meet the challenges mentioned above of uneven economic growth, unacceptably high poverty and malnutrition rates, and lagging agricultural growth. The strategy includes the following three major areas of focus: (1) Efficient and fair functioning of global and national food and agriculture systems; (2) Effective strategies and governance at the global, regional, and national levels; and (3) Enhancing pro-poor food and agriculture system innovations.